IMPLEMENTATION OF QUALITY CULTURE IMPROVEMENT PROGRAM - Siti Rukhaiyah (Universitas Islam Negeri (UIN) Sumatera Utara, 2020)
This study was conducted in Madrasah Aliyah Negeri 2 Medan. To check the validity of the data was used the triangulation technique with credibility, transferability, dependability and confirmability. The data analysis using Milles and Hubberman approaches is data reduction, presenting data and then concluding. The results of this study were three findings: 1) the planning of quality culture of the program is conducted by means of deliberations managed by the head of Madrasah with all teachers and education personnel. 2) organizing a quality culture improvement program has been well organized and 3) implementation of the quality culture improvement program runs in the desire of achievement of objectives and to give a good influence.